Evaluation of the quality of mangrove ecosystems using macrozoobenthos as bioindicators in the Southern Coast of East Java, Indonesia - Catur Retnaningdyah; Satria Cahya Febriansyah; Luchman Hakim (Society for Indonesian Biodiversity, 2022)
Abstract. Retnaningdyah C, Febriansyah SC, Hakim L. 2022. Evaluation of the quality of mangrove ecosystems using macrozoobenthos as bioindicators in the Southern Coast of East Java, Indonesia. Biodiversitas 23: 6480-6491. The mangrove ecosystem in East Java has been degraded due to land use change. Some of these mangrove ecosystems have been restored. However, the success of these restoration activities has never been evaluated. This study aimed to evaluate the quality of some mangrove ecosystems on the Southern Coast of East Java by observing the physical and chemical quality of water and macrozoobenthos that live in mangroves, especially crustaceans and gastropods, as bioindicators. Samplings were carried out on seven mangrove ecosystems, namely restored ecosystems (Cengkrong, Sine, Getem, Kondang Merak, Clungup Mangrove Conservation/CMC) and natural ecosystems as reference sites (Alas Purwo National Park/TNAP and Sempu island). The water quality parameters observed were pH, conductivity, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), nitrate, orthophosphate, Total Suspended Solid (TSS), salinity, sulfide content (H2S), oil and fat content, and dissolved lead (Pb) content. The macrozoobenthos communities observed were gastropods and crabs, while the mangrove communities monitored were only trees, using plots, each measuring 10x10 m. The results showed that some water quality parameters did not meet the sea water quality standards for marine life, namely DO and nitrate levels for all locations, H2S, and oil/fat in some locations. The quality of the restored mangrove ecosystem in the Cengkrong and CMC areas was better than that of other sites, with a Shannon-Wiener species diversity index (H') for mangrove trees of 2.796 and 2.235 and was close to the quality at the reference sites, namely Alas Purwo and Sempu island (H' 2.953 and 2.356). The H' value of macrozoobenthos in the Cengkrong and CMC mangrove ecosystem was also high (4.37 and 3.47) and almost the same as the H' value of Sempu Island and Alas Purwo (3.45 and 3.88), while in other mangrove ecosystems it ranged from 1.33 to 2.60. The species diversity of mangrove vegetation had a significant (? 0.05-0.1) to very significant (? <0.05) positive correlation with the diversity of crabs and gastropods, so the diversity of macrozoobenthos (crabs and gastropods) can be used as a bioindicator of the quality of the mangrove ecosystem.